Pengembangan Aplikasi Panduan KB Smart Kontrasepsi Non Hormonal Pada Ibu Hamil : Application Development of Smart KB Guide for Non-Hormonal Contraceptive among Pregnant Women - Aditia Silvia Fazila; Ansar Suyuti; Sri Ramadany (Poltekkes Kemenkes Palu, 2022)
Introduction: Knowledge about contraception is still relatively low for pregnant women due to limited information that only uses leaflet media as a source of information about postpartum contraception at the Kassi-Kassi Health Center so that pregnant women are unable to understand the need for their reproductive rights in making decisions to avoid inappropriate pregnancies. with what is desired or the age gap between the first and second children is too close, therefore a new breakthrough is needed in ensuring that pregnant women obtain information about contraception, especially non-hormonal contraception. Research objectives to determine the effect of developing a smart non-hormonal contraceptive KB guide application in increasing the knowledge of pregnant women. Methods: Using Research and Development (R&D), namely research and development methods used to produce certain products and test the effectiveness of these products. This type of research is Research and Development (R&D) with a simplified development model through the Quasi-Experimental Method with a two-group pre-test and post-test design. The researcher intervened/treated the subject, but it was not randomized. The technique used is purposive sampling. Results: From this study, it shows that there are differences in the results of measurements using contraceptive applications and measurements using leaflets. In the control group, there was a difference in knowledge before and after being given leaflets (p<0.05) and contributed 17.00% in increasing knowledge of pregnant women. In the intervention group, there were differences in knowledge before and after the application (p<0.05) and contributed 74.5% in increasing the knowledge of pregnant women about non-hormonal contraception. In the test results of the difference in the use of leaflets and applications, the man rank of the leaflet was 29.45% while the mean rank of the application was 65.55%. Conclusion: The effect of using educational media applications of android-based non-hormonal contraceptive smart family planning guide in increasing knowledge of pregnant women is very effective. ABSTRAK Pendahuluan: Pengetahuan soal kontrasepsi masih tergolong rendah bagi Ibu hamil dikarenakan keterbatasan informasi yang hanya menggunakan media leaflet sebagai sumber informasi mengenai kontrasepsi pasca persalinan di Puskesmas Kassi-Kassi sehingga ibu hamil tidak mampu memahami kebutuhan akan hak reproduksinya dalam membuat keputusan untuk menghindari kehamilan yang tidak sesuai dengan yang diinginkan atau jarak usia anak pertama dan kedua yang terlalu dekat, olehnya itu diperlukan suatu terobosan terbarukan dalam menjamin Ibu hamil memperoleh informasi seputar kontrasepsi khusunya kontasepsi non hormonal. Tujuan penelitian untuk mengetahui pengaruh pengembangan aplikasi panduan KB smart kontrasepsi non hormonal dalam meningkatkan pengetahuan ibu hamil. Metode: Menggunakan Research and Development (R&D) yaitu metode penelitian dan pengembangan yang digunakan untuk menghasilkan produk tertentu dan menguji keefektifan produk tersebut. Jenis penelitian Research and Development (R&D) dengan model pengembangan yang telah disederhanakan melalui Metode Quasi Eksperimental dengan rancangan penelitian two group pre test and post test design. Peneliti melakukan intervensi/ perlakuan pada subyek, tetapi tidak dilakukan randominasi (random). Teknik yang digunakan adalah purposive sampling. Hasil: Dari penelitian ini menunjukkan bahwa terdapat perbedaan hasil pengukuran menggunakan aplikasi kontrasepsi dan pengukuran menggunakan leaflet. Pada kelompok control terdapat perbedaan pengetahuan sebelum dan sesudah diberi leaflet (p<0,05) dan menyumbang 17,00% dalam meningkatkan pengetahuan ibu hamil. Pada kelompok intervensi terdapat perbedaan pengetahuan sebelum dan sesudah pemberian aplikasi (p<0,05) dan memberikan kontribusi 74,5% dalam meningkatkan pengetahuan ibu hamil mengenai kontrasepsi non hormonal. Pada hasil uji perbedaan penggunaan leaflet dan aplikasi, diperoleh man rank leaflet sebesar 29,45% sedangkan mean rank aplikasi sebesar 65,55%. Kesimpulan: pengaruh penggunaan media edukasi aplikasi panduan KB smart kontrasepsi non hormonal berbasis android dalam meningkatkan pengetahuan ibu hamil sangatlah efektif.